Synthesis and Heme Polymerization Inhibitory Activity (HPIA) Assay of Antiplasmodium of (1)-N-(3,4-Dimethoxybenzyl)-1,10-Phenanthrolinium Bromide from Vanillin - Dhina Fitriastuti; Muhammad Idham Darussalam Mardjan; Jumina Jumina; Mustofa Mustofa (Universitas Gadjah Mada, 2014)
The synthesis of (1)-N-(3,4-dimethoxy-benzyl)-1,10-phenanthrolinium bromide had been conducted from vanillin. Heme polymerization inhibitory activity assay of the synthesized antiplasmodium has also been carried out. The first step of reaction was methylation of vanillin using dimethylsulfate and NaOH. The mixture was refluxed for 2 h to yield veratraldehyde in the form of light yellow solid (79% yield). Methylation product was reduced using sodium borohydride (NaBH4) with grinding method and yielded veratryl alcohol in the form of yellow liquid (98% yield). Veratryl alcohol was brominated using PBr3 to yield yellowish black liquid (85% yield). The final step was benzylation of 1,10-phenanthroline monohydrate with the synthesized veratryl bromide under reflux condition in acetone for 14 h to afford (1)-N-(3,4-dimethoxy-benzyl)-1,10-phenanthrolinium bromide (84%) as yellow solid with melting point of 166-177 °C. The structures of products were characterized by FT-IR, GC-MS and 1H-NMR spectrometers. The results of heme polymerization inhibitory activity assay of (1)-N-(3,4-dimethoxybenzyl)-1,10-phenanthrolinium bromide showed that it had IC50 HPIA of 3.63 mM, while chloroquine had IC50 of4.37 mM. These results indicated that (1)-N-(3,4-dimethoxybenzyl)-1,10-phenanthrolinium bromide was more potential antiplasmodium than chloroquine.